Program Harmonisasi Kehidupan Relegi Dengan Penebaran Benih Ikan dan Penanaman Pohon Dalam Implementasi SDGs Di Pura Mayure Lombok - Ni Luh Sinar Ayu Ratna Dewi; I Wayan Wirata; I Made Ardika Yasa; Nanang Sutrisno; Made Wahyu Mahendra; Made Sutha Yadnya (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
The Community Service Program aims to apply the results of the analysis of the form of harmonization of religious life at Mayura Temple Lombok in the perspective of the Sustainable Development Goals (SDGs). Mayura Temple as one of the cultural heritage and center of religious activities of Hindus in Lombok has harmonized values that are reflected in the relationship between humans and God (parahyangan), humans with others (pawongan), and humans with the environment (palemahan). In carrying out the devotion, a phenomenologically direct approach to the object of service is used through observation, interviews, and documentation, as well as interfaith activities at Mayura Temple. Mayura Temple in the heart of Mataram City is proof of the moderation and harmonization of direct evidence with interfaith tree planting which is carried out as a form of ecological devotion that has an impact on the environment and common welfare. The results of the service show that religious practices at Mayura Temple have reflected the implementation of SDGs values, especially in the aspect (13) of handling climate change, aspect (14) of water and aspect (15) of the terrestrial ecosystem, this has been carried out by stocking fish and planting trees. Keywords: Mayura Temple; SDGs; fish stocking; Tree planting